Clear cell dermatofibroma on the chest wall: A case report and its diagnostic traps - Tangul Bulut; Betul Celik (Wolters Kluwer Medknow Publications, 2018)
Dermatofibromas are common lesions of the skin. Although they occur at any part of the body, they are most commonly observed on the lower legs of middle-aged women. The lesion comprises fibroblast-like cells, histiocytes, collagenous tissue, and blood vessels. Many histological variants have been defined based on the ratio of cell components and their location. These variants of dermatofibroma may cause problems during differential diagnosis between benign and malignant mesenchymal lesions of the skin and may lead pathologists to overdiagnose this lesion. Here, we report a case of clear cell dermatofibroma, which is a rare variant of dermatofibroma, together with its diagnostic traps.